Decreasing and Determining Child Mortality in Indonesia - IskandarAziz1 , Lutfi Agus Salim2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Child mortality is very important to be considered by policymakers, especially for developing countries, likeIndonesia. Child mortality rates reflect the level of health development of a country and the quality of lifeof its people. The Government of Indonesia through the 2015-2019 National Medium-Term DevelopmentPlan (RPJMN) has set a target of achieving a reduction in infant mortality of 24 per 1000 births in 2019.Achievement targets that have been made, are intended to follow the major goals of the Sustainabledevelopment goals (SDGs) in health and welfare. The government has issued a policy to reduce childmortality through programs such as Healthy Indonesia with a family approach through Permenkes no.39 of2016. Based on data obtained by the Indonesian Central Statistics Agency (BPS), it was found that neonatalmortality, infant mortality, and infant mortality from 1991 to 2017 there was a decline which meant that therewas progress in efforts to reduce child mortality. The success of the Government of Indonesia in reducingchild mortality can not be separated from the use of expert theory well. the theories used as references arethose of Mosley and Chen, and Filmer who states that children’s survival is influenced by social, economic,and biomedical factors.